Demand Forecasting and Demand Supply Management of Vegetables in India: A Review and Prospect - Reddy, A Srinivasa; CHAKRADHAR, P; P, PAVAN KUMAR; Santosh, Teja (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
Vegetable quantity arrival to market varies every day with which its prices also changes rapidly. This paper analyses the factors that affect the rapid change in prices of vegetables such as demand forecasting, demand supply management, erroneous statistics of vegetables, storage facilities, and supply chain system, etc. Government of India has no control over the production of horticultural and agricultural crops, sometimes under produced and sometimes over produced, which makes demand supply management hard-won. This paper mainly focuses on advantages of demand forecasting and demand supply management of vegetable crops and their effects on farmers and consumers. The Government should find a novel method or a system which gets crop data from farmer, does demand forecasting on day to day basis, control crop acreages, generate accurate statistics and do demand supply management of crops.